Mechanisms of social exclusion in a meritocratic pre-university school (Praxis Educativa, 2021)
The article starts from the proposal to modify the entrance to a traditional pre-university secondary school in Bahía Blanca, which, since its creation, has held the entrance exam. In 2014, the draw was partially incorporated and in 2021, in the context of the quarantine by Covid-19, the total access by draw was imposed for external applicants due to the inequalities of the meritocratic admission system. Which, according to the promoters of change, would promote the creation of an élite of "well-to-do classes" within the school, being for them the only reason for questioned educational segregation. So the present work inquires if the school dependent on the UNS has mechanisms of social inclusion that attract the enrollment that would be being excluded by the meritocratic system, or if, on the contrary, it reinforces segregation with different mechanisms of social exclusion. A qualitative methodology is used based on semi-structured interviews with teachers and principals of the analyzed institution and other schools from its city, complemented with an analysis of the regulations that rule the operation of the school and quantitative data about the access of its students. It is stated that these mechanisms exceed the admission system proposed by the school, and they correspond to an inclusive educational policy that is absent in the school studied.